Intestinal mucosal alterations parallel central demyelination and remyelination: insights into the gut-brain axis in the cuprizone model of multiple sclerosis - Ferreira, Carolina; Carvalho, Filipa; Vieira, Pedro; Alves, André; Palavra, Filipe; Almeida, Jani; Alves, Vera; Coscueta, Ezequiel; Pereira, Patrícia Dias; Pintado, Manuela; Sá, Helena; Castelo-Branco, Miguel; et al. (Frontiers in Immunology, 2025)
BackgroundThe gut-brain axis has been increasingly recognized as a critical factor in Multiple Sclerosis (MS) pathophysiology. While its role in demyelination is well documented, gut-brain axis involvement during remyelination remains largely unexplored.MethodsUsing the cuprizone (CPZ) model, which induces reversible demyelination and spontaneous remyelination upon toxin withdrawal, we investigated gut and brain changes during both disease stages in C57BL/6 mice. Animals were administered 0.2% cuprizone for 5 weeks to induce demyelination, followed by a 2-week recovery phase. Intestinal changes were evaluated through 1) gut microbiota profiling and metabolite production (short-chain fatty acids (SCFAs), indoxyl sulfate), 2) structural and barrier integrity via histology, mucus staining, and tight junction markers (ZO-1, occludin, claudin-5), 3) mucosal immunity through M1/M2 macrophage profiling and Th17/Treg ratios, and 4) expression of inflammatory and oxidative stress markers. Differences in brain demyelination/remyelination, gliosis and related molecular changes were determined using immunohistochemistry and real-time polymerase chain reaction (RT-PCR).ResultsThe demyelination peak was characterized by reduced abundance of SCFA-producing genus Akkermansia and Dubosiella, increased intestinal permeability at the level of the mucus layer and tight junction networks, and shifts in mucosal immunity toward a pro-inflammatory state characterized by M1 macrophages and Th17 cell expansion together with elevated levels of inflammatory cytokines (IL-17, IL-1β) and changes in oxidative stress-related enzymes (iNOS, HO-1, SOD1/2), all of which were partially reversed during the remyelination phase. Centrally, cuprizone-induced demyelination/remyelination and gliosis showed region-specific patterns. Neuroinflammation peaked during demyelination (TNF-α, IL-1β, IL-6, IL-17) and only partially resolved, suggesting that a balanced inflammatory response may aid remyelination.ConclusionOur findings reveal that cuprizone-induced intestinal dysfunctions temporally parallel central nervous system (CNS) lesion dynamics, disclosing temporal coordination of both compartments and highlighting gut-brain axis impact on both disease stages.